The mediation of systemic inflammation on insulin resistance and poor prognosis in non-diabetic ischemic stroke patients treated with intravenous thrombolysis - Sun, Yanli; Deng, Wei; Wang, Heng; Chen, Mingwei (Frontiers in Neurology, 2025)
Background and purposeInsulin resistance (IR) has been linked to poor stroke prognosis even in non-diabetic patients, but the underlying mechanisms remain unclear. This study aims to explore whether the association between IR and poor prognosis in non-diabetic patients with acute ischemic stroke (AIS) treated with intravenous recombinant tissue-type plasminogen activator (IV-rtPA) is mediated by systemic inflammation.MethodsIn this retrospective study, 841 consecutive patients with AIS but without a history of diabetes treated with IV-rtPA were included. IR was evaluated by means of the triglyceride-glucose index (TyG). Inflammatory markers, including the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic immune-inflammation index (SII), and inflammation prognostic index (IPI), were calculated based on blood parameters obtained within 24 h of admission. The primary outcome was poor prognosis at 90 days [modified Rankin Scale (mRS) score ≥3]. Multivariable logistic regression analysis was performed to explore the associations among TyG, inflammatory markers, and the poor prognosis. A mediation analysis was performed to examine the relationship between IR and the study outcome mediated by systemic inflammation.ResultsIn total, 107 (12.72%) had poor prognosis. After adjusting for confounders (Model 3), multivariable logistic regression analysis revealed that both TyG and NLR were significantly associated with poor prognosis [odds ratio (OR), 2.212 (95% CI, 1.564–5.617), P < 0.001; 1.059 (95% CI, 0.904–1.241), P = 0.004; respectively]. Both indicators exhibited strong predictive value for poor prognosis, with areas under the curve (AUCs) of 0.823 and 0.730, respectively. Moreover, NLR and IPI were found to partially mediate the relationship between TyG and poor prognosis, with mediation proportions of 16.5 and 13.8%, respectively. After propensity score matching (PSM), the mediating effects of inflammatory markers became more pronounced.ConclusionOur study found that insulin resistance was associated with poor prognosis in non-diabetic patients treated with IV-rtPA, and this association was partially mediated by NLR and IPI to a modest extent. These findings offer new insights into the clinical management of non-diabetic AIS patients after IV.